THE ROLE OF THE CURRATORS OF THE DEPARTMENT OF SOIL SCIENCE IN THE UPRINGING OF YOUNG (Neo Science Peer Reviewed Journal, 2023)
In this article has spoken spiritual enlightenment education and upbringing and training by teachers from soil science department.